A polymorphic transcriptional regulatory domain in the amyotrophic lateral sclerosis risk gene CFAP410 correlates with differential isoform expression - Marshall, Jack N. G.; Fröhlich, Alexander; Li, Li; Pfaff, Abigail L.; Middlehurst, Ben; Spargo, Thomas P.; Iacoangeli, Alfredo; Lang, Bing; Al-Chalabi, Ammar; Koks, Sulev; Bubb, Vivien J.; Quinn, John P. (Frontiers in Molecular Neuroscience, 2022)
We describe the characterisation of a variable number tandem repeat (VNTR) domain within intron 1 of the amyotrophic lateral sclerosis (ALS) risk gene CFAP410 (Cilia and flagella associated protein 410) (previously known as C21orf2), providing insight into how this domain could support differential gene expression and thus be a modulator of ALS progression or risk. We demonstrated the VNTR was functional in a reporter gene assay in the HEK293 cell line, exhibiting both the properties of an activator domain and a transcriptional start site and furthermore that differential expression was directed by distinct repeat number in the VNTR. These properties embedded in the VNTR demonstrated the potential for this VNTR to modulate CFAP410 expression. We extrapolated these findings in silico by utilisation of tagging SNPs for the two most common VNTR alleles to establish correlation with endogenous gene expression. Consistent with in vitro data CFAP410 isoform expression was found to be variable in the brain. Furthermore, although the number of matched controls was low there was evidence for one specific isoform being correlated with lower expression in those with ALS. To address if the genotype of the VNTR was associated with ALS risk we characterised the variation of the CFAP410 VNTR in ALS cases and matched controls by PCR analysis of the VNTR length, defining eight alleles of the VNTR. No significant difference was observed between cases and controls, we noted however the cohort was unlikely to contain sufficient power to enable any firm conclusion to be drawn from this analysis. This data demonstrated that the VNTR domain has the potential to modulate CFAP410 expression as a regulatory element that could play a role in its tissue specific and stimulus inducible regulation which could impact on the mechanism by which CFAP410 is involved in ALS.